A unified activity-based framework for one-way car-sharing services in multi-modal transportation networks. (January 2022) - Nguyen, Tri K.; Hoang, Nam H.; Vu, Hai L.
Abstract: We propose in this paper a novel activity-based bi-level mathematical model to study the interaction between one-way car-sharing services and travel demand as well as their impacts on a multi-modal network performance. At the upper level, car-sharing operators decide the price of service and the plan of relocating shared vehicles among the depots. At the lower level, driven by their own activities, the decision of travelers is made bases on the equilibrium choice of routes and associated transport modes that include private cars, public transport and shared cars. Furthermore, we develop a scalable link-based method that is capable of solving large-scale network with capacitated link flow. We show via numerical examples the impact of the one-way car-sharing services on both route choices and network performance, and demonstrate the significant improvements in the obtained solution both in terms of accuracy and computational complexity. Highlights: Formulate the optimal one-way CS problem in the multi-modal networks under the novel mathematical programming activity-based approach. Propose a novel link-based model for the above problem, which departs from the common super-network approach in the literature. Develop an efficient and scalable solution method for large-scale networks as illustrated by the numerical results. Specifically, our method can solve the Fort-Worth network consisting of 182 nodes and 441 links; the existing conventional super-network approach would not be able to tackle as it requires generating 16, 646, 400 time-dependent ATPs for only 2 OD pairs. Show the impact of FF CSS on both travel demand and system performance in terms of CSS pricing, waiting time, fleet size, and relocation. Besides, our framework can also measure the impact of the PT routes on performance and the CSS operators profit for large-scale networks.